Retranslating Philosophy: The Role of Plato's Republic in Shaping and Understanding Politics and Philosophy in Modern Greece - Fragkou, Effrossyni (Université d'Ottawa / University of Ottawa, 2012)
This thesis seeks to advance a new hypothesis for addressing retranslations, namely that the traditional explanation according to which translations become outdated and must be renewed can no longer account for all the aspects of the retranslation phenomenon. I propose to view retranslation as a means of transforming documents into monuments, of unearthing the mass of elements they contain and of making them relevant to the present and to the future. Retranslations become a source of inspiration for original philosophical texts, hence new philosophical trends or schools of thought, and for commentaries on the translation and its agents, all of which reflect the place and time where they emerge, thus shaping symbols of self-representation, collective consciousness, memory, and identity. I test this hypothesis through the exploration of 20th century Modern Greek retranslations of Plato’s Republic and through the examination of the diachronic and synchronic values of key political and philosophical elements of Plato’s system within the retranslations. These retranslations reflect not only how Plato’s philosophy is perceived by the modern Greek philosophical and political environment, but also whether they represent and prolong the canonical discourse on classical philosophy or introduce a more critical turn. I explore a case of a philosophical text whereby key elements of the Republic become a source of inspiration to answer basic questions of justice and polity from a modern point of view. I conclude that retranslations project the aspirations, fears, and values of the time and space in which they emerge while using the openness of the text to add extra layers of interpretation and meaning. Almost all retranslations and their corresponding paratext maintain a consistent referential relationship with one another and with other political and philosophical texts produced during the same period. The link that ties these texts together is not necessarily chronological. It also depends on the discursive approach adopted; the translator’s political or philosophical affiliation; the degree of canonicity of each translation and translator, and the prevailing ideologies of the society in which retranslations emerge. A classical work can become either a vibrant document used to promote, sustain, and revive dominant discourses on politics, national identity or philosophy or, alternately, a reactionary document that voices concerns over the relevance of the canonical or traditional discourse with which the original is equated.
Keywords: Retranslation; Philosophy; politics; education; Plato; Republic; Greek Studies; Translation studies